Typology and Ranking of Different Price Discount Formats: A Mixed-Methods Study - Mohsen Nazari; Elham zafarianpoor (‫مدیریت بازرگانی)
Objective In recent years, various approaches have been used to implement marketing activities and achieve companies' sales goals. One of the most widely adopted strategies is using different discount formats. A key challenge for companies is the effective utilization of product-appropriate discount formats. The lack of coherent knowledge about the types of discount formats and their impact on sales motivates this research. This study employed a mixed-methods approach and was conducted in two consecutive phases: qualitative and quantitative. One of the key issues in price discounts is framing them correctly and using appropriate formats that align with the product and discount conditions to maximize their effectiveness. Therefore, it is crucial to provide a comprehensive list of discount format types and consult sales experts to assess their effectiveness.